The prevalence of epilepsy among a rural Kenyan population. Its association with premature mortality. - Snow, R; Williams, R; Rogers, J; Mung'ala, V; Peshu, N (1994)
During a two year community-based investigation of mortality 3.5% of the deaths to individuals over the age of 5 years were reported by bereaved relatives to have occurred to epileptics and 77% of these deaths were thought to have occurred whilst the patient was in status epilepticus. This prompted us to determine the prevalence of epilepsy in this rural population by interviewing 7,450 residents of a pre-defined study area. The prevalence of 'Kifafa' or 'Vitsala', two local words used to describe epilepsy, but later confirmed through detailed interviews, was 0.4%. This prevalence is clearly an underestimate of the true prevalence of epilepsy in this population but is probably higher than prevalences reported in developed countries. Anti-convulsant prophylaxis is available at the district hospital but this service is only sporadically used by epileptics in this population. Uncontrolled and poorly managed epilepsy may result in an increased risk of premature mortality among epileptics living in this community.